Arsenic speciation in aquatic organisms collected from south-central Puget Sound urban lakes in 2018 and 2019 - Erin A Hull; Rebecca B Neumann; Julian D Olden; James E Gawel (PANGAEA, 2021)
Between 2 and 6 littoral sediment samples were collected in 2018 and 2019 from nearshore (1-2 m depth) in each lake using a dredge (Wildco Petite Ponar Stainless Steel Grab) and dried at 60 °C overnight and homogenized using a porcelain mortar and pestle. Oven-dried sediment samples were digested using a microwave-assisted (CEM MARS 5) total digestion protocol (modified EPA method 3015a). Concentrations of total arsenic in digested sediment samples were determined by inductively-coupled plasma mass spectrometry (ICP-MS) on an Agilent 7900 at the University of Washington Tacoma.